The role of electrons during the martensitic phase transformation in NiTi-based shape memory alloys. (May 2022) - Kunzmann, A.; Frenzel, J.; Wolff, U.; Han, J.W.; Giebeler, L.; Piorunek, D.; Mittendorff, M.; Scheiter, J.; Reith, H.; Perez, N.; Nielsch, K.; Eggeler, G.; et al.
Abstract: Nickel-titanium (Ni50 Ti50 )-based alloys are the most important representatives of the class of shape memory alloys. However, the role of electrons in this transformation leading to the shape memory effect is not yet overall understood. Here we show how the alloy composition affects resistivity, Hall coefficient and Seebeck coefficient as well as Terahertz reflectance during the martensitic phase transformation. Remarkably, the charge carrier density obtained by Hall measurements is reduced by almost one order of magnitude in the martensitic phase compared to the austenitic phase, and its reduction starts well before the actual transformation. This reduction of the charge carrier concentration is also seen in the obtained Terahertz spectra. Together with this reduction of the charge carrier density, the charge carrier mobility increases at the phase transformation. This means that neither additional scattering events nor altered electron-phonon coupling play a dominant role for the interpretation of the anomaly in the electrical resistivity. We further utilize these transport data to deduce the electronic entropy contribution to this phase transformation and compare it to the total entropy contribution obtained by heat capacity measurements. The electronic entropy contribution directly scales with the martensitic start temperature and reaches over 30% of the total entropy contribution for compositions close to equiatomic Ni50 Ti50 . The experimental data points towards a partly transfer of electron density from the free electron gas (austenite) to the bonding (martensite). We interpret this in terms of a formation of a charge density wave phase that would fit to both findings, the strong reduction of charge carriers, as well as the high electronic entropy contribution to this phase transformation. Graphical abstract: Image 1 Highlights: Resistivity, Seebeck, Hall measurements and THz spectroscopy was performed on several Ni50+x Ti50-x compositions. A steep decrease of the charge carrier density at the phase transition was shown. The charge carrier mobility increases simultaneously, causing the resistance anomaly. The electronic entropy contribution by Seebeck and Hall measurements can reach up to approximately 30% of the total entropy by specific heat measurements. We conclude that the well-known anomaly of the resistivity is caused by the formation of a charge density wave phase at the martensitic phase transition.